A melhora da reconsolidação da memória induzida por espermidina envolve a proteína cinase dependente de cálcio - Girardi, Bruna Amanda (2015)
The reactivation of a memory results in its destabilization, requiring a process of memory reconsolidation to maintain it. Spermidine is an endogenous aliphatic amine with polycationic structure that modulates N-methyl-D-aspartate (NMDA) receptor activity and improves memory. Recent evidence suggests that systemic administration of spermidine improves the reconsolidation of fear memory. Here we determined whether the calcium-dependent protein kinase (PKC) signaling pathway is involved in the improvement of fear memory reconsolidation induced by intrahippocampal (ih) administration of spermidine in rats. Male Wistar rats were trained in a fear conditioning apparatus using a 0.4 mA footshock as unconditioned stimulus. Twenty-four hours after training, animals were re-exposed to the apparatus in the absence of shock (reactivation session). Immediately after the reactivation session, spermidine (2-200 ρmol/site); the PKC inhibitor, 3-[1- (dimethylaminopropyl)indol-3-yl]-4-(indol-3-yl) maleimide hydrochloride (GF 109203X, 0.3 - 30 ρg/site); the antagonist of the polyamine-binding site at the NMDA receptor, arcaine (0.2 - 200 ρmol/site) or the PKC activator, phorbol 12-myristate 13-acetate (PMA, 0.02 - 2 nmol/site) were injected intra-hipocampally (i.h.). Testing was carried out in the same apparatus, twenty-four hours after reactivation. Freezing scores at testing were considered a measure of memory. While the post-reactivation administration of spermidine (20 and 200 ρmol/site) improved, GF 109203X (1, 10 and 30 ρg/site) impaired memory reconsolidation. GF 109203X (0.3 ρg/site) prevented spermidine (200 ρmol/site)-induced improvement of memory reconsolidation. The post-reactivation administration of arcaine (200 pmol/site) impaired and PMA (2 nmol/site) improved memory reconsolidation. PMA (0.2 nmol/site) prevented arcaine (200 ρmol/site)-induced impairment of memory reconsolidation. The protein synthesis inhibitor anisomycin (2 μg/site) prevented spermidine (200 ρmol/site)-induced improvement of memory reconsolidation. These drugs had no effect on memory if they were administered in the absence of reactivation. These results suggest that the enhancement of memory reconsolidation induced by the administration of spermidine involves PKC activation.